miR-31-3p functions as a tumor suppressor by directly targeting GABBR2 in prostate cancer - Choi, Sujin; Lee, Soonchul; Han, Young-Hoon; Choi, Junwon; Kim, Isaac; Lee, Jusung; An, Hyun-Ju (Frontiers in Oncology, 2022)
MicroRNAs are key regulators of gene expression in tumorigenesis. In this study, we investigated the tumor-suppressive function of miR-31-3p. Analysis of the Gene Expression Omnibus database revealed that the expression of miR-31-3p in prostate cancer tissues is lower than that in adjacent normal tissues from patients with prostate cancer. Moreover, miR-31-3p induces apoptosis in DU145, PC-3, and LNCap prostate cancer cells, while those transfected with miR-31-3p exhibit significantly decreased cell proliferation, migration, invasiveness, and tumor sphere-forming ability, as determined using the cell counting kit-8, transwell, and sphere-forming assays. Further analysis revealed that GABBR2 is a direct target of miR-31-3p. Within a DU145 xenograft murine model, intratumoral injection of a miR-31-3p mimic suppresses tumor growth. Taken together, the findings of this study suggest that miR-31-3p performs a novel tumor-suppressive function in prostate cancer and may represent a novel target for anti-prostate cancer miRNA therapeutics.